P-030 Low nihss M1 occlusion stroke: preliminary single-center outcomes of medical management versus thrombectomy. (22nd July 2018) - Nasiri, A; Burns-Benggon, J; Kim, P; Gezalian, M; Oyoyo, U; Hoss, D; Jacobson, J
Abstract : Background and purpose: The clinical constellation of mild acute stroke symptoms and M1 occlusion occurs not infrequently. Whereas thrombectomy is clearly beneficial for ELVO with NIHSS ≥8, which is predominantly embolic, milder presentation suggests chronic etiology, namely intracranial atherosclerotic disease (ICAD), for which thrombectomy has not been shown an effective treatment. This retrospective study reports the discharge outcomes of medical management versus mechanical thrombectomy in a retrospective cohort of patients with low NIHSS M1 occlusion stroke. Methods: We performed a retrospective chart review of patients presenting to our institution between 2013 and 2018 with hyperacute M1 occlusion and NIHSS ≤9. Patients were divided into three groups by presenting NIHSS: very low (VLPN; NIHSS ≤4), intermediate low (ILPN; 4< NIHSS >9), and upper low (ULPN; NIHSS=9). The primary outcome was difference in clinical neurologic status (NIHSS) between discharge and presentation, dichotomized into Stable/Improved (≤0) or Worsened (>0). Groupwise difference in change in NIHSS from presentation to discharge was assessed for statistical significance nonparametrically (Kruskal-Wallis). Results: Twenty-nine patients (17 male, 12 female) presented with hyperacute M1 occlusion stroke and NIHSSS ≤9. The VLN group showed higher rate of diabetes (p=0.043) and a trend toward higher prevalence of alcohol use (p=0.183); the groups were otherwise comparable. At discharge, 8/8 VLPN patients (all medically managed) showed stable/improved NIHSS. Of the ILPN patients, 10 were stable/improved and 7 were worsened; of the 8 managed medically, 4 were neurologically stable/improved at discharged versus 4 worsened; and of the 9 who received thrombectomy, 6 were stable/improved versus 3 worsened. 4/4 of the ULPN patients received thrombectomy; at discharge 3 were stable or improved, whereas 1 was worsened. The difference in change in NIHSS between the three groups was not statistically significant (p=0.847), although it trended towards significance when stratifying by treatment (figure 1; p=0.156). Conclusion: These preliminary data suggest that patients with M1 occlusion stroke and very low presentation NIHSS (<5) are likely to do well with medical management. In this study, the highest frequency of worsening neurologic status was observed in patients with presenting NIHSS between 4 and 9, with a trend toward better outcome after thrombectomy in this range. Further study is needed to guide treatment for low NIHSS M1 strokes. Disclosures: A. Nasiri: None. J. Burns-Benggon: None. P. Kim: 6; C; AUR GE Radiology Research Academic Fellowship. M. Gezalian: None. U. Oyoyo: None. D. Hoss: None. J. Jacobson: 4; C; Genelux, Inc.